MODEL PROSES INOVASI PEMBANGUNAN KAMPUNG GLINTUNG KOTA MALANG - Tri Yuliyanti; Eddy Priyanto (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2019)
Glintung RW 23 is a dense village with several environmental and social problems. Responding to this problem, RW 23 Institutions and villagers agreed to innovate, create an environmentally friendly village and, at the same time, address existing social problems. The purpose of this study is to develop a model for the implementation phase-in of the development innovation process in Glintung village, Malang City accordingly. Data was extracted by in-depth interviews and documentation and then analyzed qualitatively. The results of this study provide examples of steps that are appropriate for the village development innovation process that is appropriate and applies to all village areas that carry out the same development.Â